Smart Healthcare: The Role of Digital Health in Modern Medicine - Nidha Shapoo; Naveed Shapoo; Abdul Rehman; Noella Boma (Health Care Science)
ABSTRACT Digital health is transforming healthcare by integrating advanced technologies to make healthcare more accessible, efficient, and personalized. From electronic health records, telemedicine, wearable devices, and artificial intelligence to the recent smart hospitals, digital health is improving patient care and outcomes while reducing healthcare costs. However, the integration of digital health faces several challenges, including data privacy, cybersecurity risks, and inequitable access to technology. This article provides an overview of the current state of digital health, key challenges in implementation, and potential solutions to maximize the benefits of digital health and ensure efficient, equitable, and patient‐centered healthcare in the future.